Does Symbiosis with Bacteria Influence the Transition to Multicellularity in Algae? - Almurad,Tamim (2025)
The transition from unicellular to multicellular life remains one of evolution’s biggest mysteries. In this study we introduce symbioses with bacteria as a possible player. We use metagenomic analysis to investigate bacterial communities associated with Volvocine green algae, a model system for multicellularity. We compared bacterial communities of 34 algal species (21 unicellular and 13 multicellular). We developed a new workflow for metagenomic profiling (MBO100) that significantly reduces false positives produced by popular tools in the field. Our results reveal that the composition of bacterial communities is broadly similar between multicellular and unicellular species, but some bacterial families showed specificity to unicellular algae, such as Roseobacteraceae. However, many bacteria were specific to certain algae species making it challenging to separate the effect of host identity from associations with multicellularity. To solve this issue, further studies are required to assess functional interactions between bacteria and algal hosts.